Catalyst for the reduction of NO to Nwith hydrogen under NOx oxidation conditions - (:unkn) unknown (My University, 2005)
The invention relates to a novel catalyst having excellent activity, selectivity and stability for reducing nitric oxide to gas nitrogen, with hydrogen being used as a reducing agent, in the low temperature range 100–200° C. and in the presence of an excess of oxygen (e.g. 5% vol), H2O (5% vol) and/or SO2 (20 ppm) in the supply. The inventive catalyst consists of platinum crystals which are in contact with the phases of a mixed MgO and CeO2 medium or in the form of platinum supported on the mixed MgO—CeO2 medium which has already been sulphated in a selective manner. The Pt/MgO—CeO2 catalyst can be used to obtain NO conversion levels which are greater than 40% and nitrogen selectivity values of greater than 80% under NOx oxidation conditions in the 100–400° C. temperature range and for a surface contact time of 0.045 s. In particular, full NO conversion is obtained as well as N2 selectivity levels of 83% at 150° C. with a reaction mixture of 0.25% NO/1% H2/5% O2/5% H2O/He.
Keywords: Utilizing Solid Sorbent, Catalyst, Or Reactant (423/239.1); Novel catalyst; Nitric oxide; Platinum Group Metal And Of Iron Group (i.e., Ru, Rh, Pd, Os, Ir, Or Pt And Fe, Co Or Ni) (502/326); Group Ii Metal Containing (i.e., Alkaline Earth, Be, Mg, Zn, Cd Or Hg) (502/328); Gas nitrogen; Cerium (502/304); Of Group Ii (i.e., Alkaline Earth, Be, Mg, Zn, Cd Or Hg) (502/340); Miscellaneous (e.g., Carrier Or Support Per Se Or Process Of Making, Etc.) (502/439); Palladium Or Platinum (502/339); B01J 23/00 (20060101); B01J 23/42 (20060101); B01J 23/44 (20060101); B01J 21/04 (20060101); B01J 8/00 (20060101)